Monitoring Dan Implementasi Sistem Otomasi Real Time Kualitas Air Tambak Menggunakan Web - M. Sifa'un Ni'am; Sabriansyah Rizqika Akbar; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Ponds farmers experience anxiety because of the frequent occurrence of poor water quality. With the current conditions, the fish farmers are very difficult to get good quality clean water. Changing weather conditions can exacerbate pond water quality, conditions like this can also make fish farmers unsettled, because current pond farmers depend on weather conditions and environmental conditions directly. Based on these problems, research is used to at least control the quality of water by using 2 sensors, namely the LDR sensor to determine the value of turbidity in the water, and the DS18B20 temperature sensor to determine the pond water temperature. Using the Arduino Uno microcontoler and ESP8266 module to transmit data from the two sensors readings to the Thingsboard web server. Readings from two sensors will appear on Thingsboard in the form of charts and graphics. From the results of this monitoring system test shows the results that the system will provide the results of the sensor readings, the LDR sensor gives results if the clear water gives a value smaller than turbid water, and the temperature sensor gives an average temperature value of the sensor of 35, 55 Â° C and the average temperature value of the thermometer reading is 35.44 Â° C, and the average of the error value is 0.46%. The delay results from the ESP8266 test give the average delay time of 1.7s.